Semiótica y teoría de la organización. El discurso de una práctica administrativa - González Morera, Héctor (2004)
The articIe recreates part of the group Tel Quel's semiotic proposal in the first part, trying to incorporate afterwards, dominant ideological elements in the constitution of stocks of knowledge in the administrative sciences, reinforced by the definition of a behavioral code that norms the process of production of these scientific goods. In doing so, the most challenging epistemological debates of the second half of the twentieth century are revisited and a broad picture of its determination, in the field of administrative sciences is sketched, from the point of view of one of its more significant objects, the modern organizations. Significant concIusions are drawn upon considering the subordinate development of organizational theory and the marginal texts that binds it. This allows for a critical analysis of the theory and the consideration of both, the paradigrns cooperation and participation within the field.